Lost in Hong Kong: Hong Kong as a "bizarre national redemptive space" for the new Chinese middle class. Issue 2 (5th September 2017) - Lok, Peter
Abstract : Purpose: The purpose of this paper is to explore how a neo-liberal nationalist discourse of China imagines the spatial identity of the post-1997 Hong Kong with reference to Lost in Hong Kong, a new Chinese middle-class film in 2015 with successful box office sales. Design/methodology/approach: Textual analysis with the aid of psychoanalysis, postcolonial studies and semiotics is used to interpret the meaning of the film in this study. The study also utilizes the previous literature reviews about the formation of the Chinese national identity to help analyze the distinct identity of the Chinese middle class today. Findings: The discussion pinpoints how the new Chinese middle class as neo-liberal nationalists take Hong Kong as a "bizarre national redemptive space". While Hong Kong is cinematically constructed as such a national other, this paper argues that the Hong Kong in question stands not for itself but in a form of "reverse hallucination" for pacifying the new Chinese middle class' trauma under the rapid neo-liberalization of China in the 1990s. Originality/value: This paper shows the new of formation of the Chinese nationalist's discourse, especially the new Chinese middle-class discourse on Hong Kong after 1997.